Graphene-Based Kinetic Promotion of Gas Hydrate Formation - Sun, Meng-Ting; Zhang, Guo-Dong; Wang, Fei (Frontiers in Chemistry, 2020)
Gas hydrate technology holds great potentials in energy and environmental fields, and achieving the efficient gas hydrate formation is critical for its industrial applications. Graphene is a novel carbon-based nano-structured material with excellent thermal conductivity and large specific surface area, therefore the graphene-based materials might be feasible for promotion to gas hydrate formation and has aroused tremendous attention. On this account, to evaluate the current research on graphene-based promotion to gas hydrate formation, a review aiming at the existing studies involving in graphene-based promoters for gas hydrate formation is presented in this work. Here, the studies applying various types of graphene-based promoters for gas hydrate formation are listed and mentioned, the peculiar properties of graphene-based promoters are discussed and the promotion mechanisms are analyzed. Through this review, a comprehensive insight into graphene-based promotion to gas hydrate formation can be obtained, which can guide the design and applications of novel graphene-based promoters, and might contribute to achieve the efficient gas hydrate formation.